Effect of Moringa oleifera, Bacillus amyloliquefaciens, and Their Combination on Growth Performance, Digestive Enzymes, Immunity, and Microbiota in Nile Tilapia (Oreochromis niloticus) - Mingxuan Guan; Junfeng Guan; Haotian Zhang; Dikuang Peng; Xiaotong Wen; Xiaoyong Zhang; Qing Pan (Aquaculture Nutrition)
To exploit aquatic animals’ feed resources and functional ingredients and additives, this experiment investigated the effects (a 2 × 2 factorial trial) and mechanism of woody plants and probiotics on Nile tilapia. Each treatment group was randomly assigned triplicate nets of 40 fish (initial body weight of 35.04 ± 0.01 g) in 12 tanks for 56 days. Fish were fed four diets, including a CON–CON diet (with no supplementation) and CON–Ba (basal diet + 1 × 107 CFU/g B. amyloliquefaciens), MO-CON (basal diet + 10% Moringa oleifera) and MO-Ba (basal diet + 1 × 107 CFU/g B. amyloliquefaciens + 10% Moringa oleifera) until apparent satiation (2 meals/day). The results showed that the MO diet had a lower feed conversion ratio than the non-MO diets (P<0.05). The weight gain in the Ba group was significantly higher than those in the groups without Ba treatment (P<0.05). Both MO and Ba improved the morphological indices when applied individually (P<0.05). Ba supplementation improved the activities of digestive enzymes (P<0.05). MO significantly upregulated the gene expression of TNF-α, IL-6, IL-10, and C3 in the spleen of Nile tilapia (P<0.05), while Ba significantly upregulated the gene expression of IL-6 and C3 (P<0.05). The microbiological analyses showed that the abundances of beneficial bacteria increased, and the relative abundances of pathogenic bacteria decreased in fish-fed MO. In conclusion, dietary MO and Ba can effectively improve the immunity of Nile tilapia, while Ba can enhance the activities of digestive enzymes. The synergistic effect of MO and Ba on the intestinal microbiota of Nile tilapia promotes growth, thus showing promising application prospects.